(untitled) (Pedagogy of Higher and Secondary Education, 2003)
In the article, the pedagogical trend comes out as the subject of exploration by many investigators. The author argues the necessity of scientific basis and organized the plan with the purpose of exposing and training the student’s pedagogical trends as the foundation of forming future teachers’ pedagogical traditions.